Kinerja Manajemen Rantai Pasok Keripik Lokan Pada Industri Kecil di Aceh Singkil - Ramadhani, Nabila; Herlina, Sella Fauziati; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The purpose of this study was to determine the performance of the supply chain in the Lokan Shell Chips Small Industry in Singkil City. conducted in Singkil City, with 3 respondents. The method used is a qualitative analysis to identify the supply chain and identify and analyze the supply chain, the supply chain uses the SCOR (Supply Chain Operations Reference) method, the supply chain of the measured attributes, namely supply chain reliability, supply chain response, and supply chain in small industries. lokan chips in aceh singkil.